Mediating role of referential thinking in the relationship between perfectionism and obsessive-compulsive disorder among gifted students - Camelia Sadati (Shahid Beheshti University of Medical Sciences, 2023)
Background: Obsessive-compulsive disorder (OCD) is a prevalent condition of psychological dysfunction in students and causes anxiety in them. The present study aimed to investigate the mediating role of referential thinking in the relationship between perfectionism and OCD among gifted students. Methods: The statistical population of this descriptive correlation study included all gifted high school students in Tehran in 2020. Multistage random cluster sampling was employed to select 110 students (55 males and 55 females), and structural equation modeling was used for data analysis. The research instruments included the Perseverative Thinking Questionnaire (PTQ), Frost Multidimensional Perfectionism Scale (FMPS), and Maudsley Obsessive-Compulsive Inventory (MOCI). Results: Referential thinking mediated the relationship between perfectionism and OCD in an indirect, negatively significant manner (P<0.001). Perfectionism and referential thinking were directly and significantly correlated; however, referential thinking had a significant negative relationship with OCD (P<0.001). According to the results, perfectionism predicted 11% of the variance in referential thinking, while perfectionism and referential thinking together predicted 17% of the variance in OCD. Moreover, the findings did not reveal a significant direct relationship between perfectionism and OCD. Conclusion: Perfectionism and referential thinking contribute to the alleviation of OCD in gifted high school students. Intellectually gifted students can adopt creative coping techniques, which can mitigate the adverse effects of OCD, as they have high levels of creativity, self-awareness, and sensitivity.